Patterns of within-host spread of Chlamydia trachomatis between vagina, endocervix and rectum revealed by comparative genomic analysis - Joseph, Sandeep J.; Bommana, Sankhya; Ziklo, Noa; Kama, Mike; Dean, Deborah; Read, Timothy D. (Frontiers in Microbiology, 2023)
Chlamydia trachomatis, a gram-negative obligate intracellular bacterium, commonly causes sexually transmitted infections (STIs). Little is known about C. trachomatis transmission within the host, which is important for understanding disease epidemiology and progression. We used RNA-bait enrichment and whole-genome sequencing to compare rectal, vaginal and endocervical samples collected at the same time from 26 study participants who attended Fijian Ministry of Health and Medical Services clinics and tested positive for C. trachomatis at each anatomic site. The 78 C. trachomatis genomes from participants were from two major clades of the C. trachomatis phylogeny (the prevalent urogenital and anorectal clade and non-prevalent urogenital and anorectal clade). For 21 participants, genome sequences were almost identical in each anatomic site. For the other five participants, two distinct C. trachomatis strains were present in different sites; in two cases, the vaginal sample was a mixture of strains. The absence of large numbers of fixed SNPs between C. trachomatis strains within many of the participants could indicate recent acquisition of infection prior to the clinic visit without sufficient time to accumulate significant variation in the different body sites. This model suggests that many C. trachomatis infections may be resolved relatively quickly in the Fijian population, possibly reflecting common prescription or over-the-counter antibiotics usage.